1982
DOI: 10.1002/mrc.1270200308
|View full text |Cite
|
Sign up to set email alerts
|

Comparative NMR study of rhamnobioses—applications

Abstract: L-Rhamnose is widely distributed in many plant families, where it occurs either alone as in quercetin, associated with D-glucose or D-galactose as in rutin or robinin, or as rhamnobioses in heterosides such as alaternin, xanthorhamnin and catharticin.NMR spectroscopy, both proton' and 13C2-4, has played an important role in determining the structure of the aglycone in flavonoids but it is more difficult to identify the sugar sequence, the point of attachment of the oligosaccharide to the aglycone and the posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…COSY correlations from H-2'' to H-6'', in conjunction with the HMBC correlation of H-5'' to C-1'' suggested the presence 6-deoxyhexose sugar moiety. This was identified to be α-rhamnopyranose by comparison of the 1 H and 13 C spectroscopic data with those reported in the literature, 16 Lahoum et al 17 have recently published two bipyridine glycosides isolated from another Saccharothrix strain. One of the glycosides, cyanogriside J, has a similar structure to 1.…”
Section: Resultsmentioning
confidence: 71%
“…COSY correlations from H-2'' to H-6'', in conjunction with the HMBC correlation of H-5'' to C-1'' suggested the presence 6-deoxyhexose sugar moiety. This was identified to be α-rhamnopyranose by comparison of the 1 H and 13 C spectroscopic data with those reported in the literature, 16 Lahoum et al 17 have recently published two bipyridine glycosides isolated from another Saccharothrix strain. One of the glycosides, cyanogriside J, has a similar structure to 1.…”
Section: Resultsmentioning
confidence: 71%
“…The 7-O-glycosylation was deduced from the UV data and confirmed by the presence of a signal C -7 at δ = 162.1 [15][16][17]. The (1→2) interglycosidic linkages were deduced from the downfield shift of carbon at position 2 (C-2'' at δ = 77.3 and C-2''' at δ = 77.2) and upfield shift of carbons at position 3 (C-3'' at δ = 71.1 and C-3''' at δ = 71.6) of the two non-terminal rhamnopyranoses [18]. This was ascertained from the NOESY spectrum which illustrated a relation between H-1''' at δ = 5.52 and H-2'' at δ = 3.81 and another relation between H-1'''' at δ = 5.28 and H-2''' at δ = 3.96.…”
Section: Present Studymentioning
confidence: 99%
“…The 7-O-glycosylation was deduced from the UV data and confirmed by the presence of a signal C-7 at δ = 161.4. The downfield shift of C-2'' of the internal rhamnopyranose moiety at δ = 79.5 indicated that the interglycosidic linkage between the two rhamnopyranose moieties is a 1→2 linkage [18]. HRESI-MS spectrum showed an ion peak at m/z 579.1692 corresponding to [ .…”
Section: Present Studymentioning
confidence: 99%
“…These epoxides afforded the derivatives 20a [44] and 21a [45] via S N 2 ring opening with MeOH at the anomeric carbon. The minor derivatives 20b [46] and 21b [47] are derived from the diastereomeric b-epoxides. Finally, the MTO-catalyzed epoxidation of d-arabinal derivatives occurred with high stereoselectivity.…”
Section: Full Papersmentioning
confidence: 99%